Hidrodeoksigenasi Pirolisis Kayu Ketapang (Terminalia Catappa L) Menjadi Bio-Oil Menggunakan Katalis Mo/Lempung - Andi Mulya Adha; Syaiful Bahri; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bio-oil can be produced by hydrodeoxygenation pyrolysis of terminalia catappa wood using Mo/Clay catalyst. Objective of this research is to produce bio - oil from catappa wood using hydrodeoxygenation pyrolysis method, determine the effect of hydrodeoxygenation temperature and percentage of Mo/clay catalyst to the yield of bio - oil produced, as well as determine the effect of hydrodeoxygenation pyrolysis on physical properties and chemical properties of bio - oil produced. Hydrodeoxygenation pyrolysis process was carried out using catappa woody biomass 50 grams with -100 + 200 mesh sieve size, silinap 500 ml, variation Mo / clay catalyst to the biomass amounted to 0 %; 0,5 %; 1,5 % and 2,5 % by weight to biomass and hydrodeoxygenation pyrolysis temperature variations are: 300, 310, 320, and 330°C. Results of this study produced bio - oil yields the largest on the use of Mo / clay catalyst 1,5 % by weight to biomass and temperature of 320°C which is 65,477 %. Characterization of physical properties of bio - oil measured of density of 0,909 g /ml, 1,797 cSt viscosity, acid number 30,089 mg NaOH / gram sample, 48 °C flash point and calorific value 44,725 MJ / kg. Respectively the characterization of the chemical properties of bio - oil using Gas Chromatography - Mass Spectroscopy (GC - MS) obtained some dominant chemical components such as: (2,4,4-trimethyl, 2-pentene), (2,2,4,4-tetramethyl, Pentane), (3 (3,3-dimethyl butyl), Cyclohexanone), (5,5-dimetyl, 2-Hexene), and (1-propene, 2-methyl, tetramer). Keywords: bio – oil, catappa wood, hydrodeoxygenation pyrolysis, Mo/clay catalyst